Dl‐3‐n‐butylphthalide promotes synaptic plasticity by activating the Akt/ERK signaling pathway and reduces the blood–brain barrier leakage by inhibiting the HIF‐1α/MMP signaling pathway in vascular dementia model mice. (8th February 2023) - Che, Ping; Zhang, Juan; Yu, Mingqian; Tang, Ping; Wang, Yanhui; Lin, Aolei; Xu, Jing; Zhang, Nan
Abstract: Aims: DL‐3‐n‐butylphthalide (NBP) exerts beneficial effects on global cognitive functions, but the underlying molecular mechanisms are still poorly understood. The present study aimed to investigate whether NBP mediates synaptic plasticity and blood–brain barrier (BBB) function, which play a pivotal role in the pathogenesis of vascular dementia (VaD), in a mouse model of bilateral common carotid artery stenosis (BCAS). Methods: NBP was administered to model mice at a dose of 80 mg/kg by gavage for 28 days after surgery. Cognitive function was evaluated by behavioral tests, and hippocampal synaptic plasticity was evaluated by in vivo electrophysiological recording. Cerebral blood flow (CBF), hippocampal volume, and white matter integrity were measured with laser speckle imaging (LSI) and MRI. In addition, BBB leakage and the expression of proteins related to the Akt/ERK and HIF‐1α/MMP signaling pathways were assessed by biochemical assays. Results: NBP treatment alleviated cognitive impairment, hippocampal atrophy, and synaptic plasticity impairment induced by BCAS. In addition, NBP treatment increased CBF, promoted white matter integrity, and decreased BBB leakage. Regarding the molecular mechanisms, in mice  with BCAS,  NBP may activate the Akt/ERK signaling pathway, which upregulates the expression of synapse‐associated proteins, and it may also inhibit the HIF‐1α/MMP signaling pathway, thereby increasing the expression of tight junction (TJ) proteins. Conclusion: In conclusion, our results demonstrated the therapeutic effects of NBP in improving cognitive function via a wide range of targets in mice subjected to BCAS. Abstract : DL‐3‐n‐butylphthalide may improve cognitive function via mediating the Akt/ERK and HIF‐1α/MMP signaling pathways in a mouse model of bilateral common carotid artery stenosis.